2012
DOI: 10.1159/000337571
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Patterns of Treatment, and Control of Hypertension in Predialysis Patients with Chronic Kidney Disease

Abstract: Background/Aims: Data on the prevalence, treatment and control of hypertension in patients with advanced chronic kidney disease (CKD) are limited. This study aimed to examine the above factors in a cohort of predialysis patients. Methods: During a period of 4 months, we recorded information on blood pressure (BP), comorbidities, medications and related parameters of patients followed up in the Low-Clearance Clinic of our Department. Control rates of hypertension were calculated at two thresholds: <130/80 and <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 83 publications
2
30
1
1
Order By: Relevance
“…In an analysis of 3612 participants in the Chronic Renal Insufficiency study, 83% of individuals with hypertension were taking at least two classes of antihypertensive medication, with 26% and 32% of participants taking antihypertensive medications from three and four or more classes, respectively (3). Consistent with this finding, 87% of 238 predialysis CKD patients in a recent study were taking at least two antihypertensive medications, with 34% of patients taking three antihypertensive medications and 33% of patients taking four or more antihypertensive medications (13). However, the prevalence of aTRH was not evaluated in these prior studies.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In an analysis of 3612 participants in the Chronic Renal Insufficiency study, 83% of individuals with hypertension were taking at least two classes of antihypertensive medication, with 26% and 32% of participants taking antihypertensive medications from three and four or more classes, respectively (3). Consistent with this finding, 87% of 238 predialysis CKD patients in a recent study were taking at least two antihypertensive medications, with 34% of patients taking three antihypertensive medications and 33% of patients taking four or more antihypertensive medications (13). However, the prevalence of aTRH was not evaluated in these prior studies.…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, most people with CKD and hypertension take multiple classes of antihypertensive medication (3,13). In an analysis of 3612 participants in the Chronic Renal Insufficiency study, 83% of individuals with hypertension were taking at least two classes of antihypertensive medication, with 26% and 32% of participants taking antihypertensive medications from three and four or more classes, respectively (3).…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Population studies with CBP measurements have shown hypertension prevalence around 70% to 80% in patients with stage 1 CKD, whereas in stages 4 and 5 before initiation of dialysis, this rate increases to >95%. 25,26 CBP measurements are less than ideal to guide hypertension treatment in CKD. They are misleading in a large proportion of patients because as much as 40% of those who are apparently normotensive by CBP turn out to be hypertensive by HBP.…”
mentioning
confidence: 99%
“…Meanwhile, authors worldwide agree that the prevalence of arterial hypertension in pre-dialysis CKD patients can reach from 43 to95% [12,13] and stands as an important risk factor for progression and cardiovascular disease [14]. Ambulatory blood pressure monitoring stands as an useful tool in arterial hypertension diagnosis protocol [15,16] and seems to be superior to home or office blood pressure monitoring due to a lower risk of masked or white-coat hypertension, although this fact remains controversial.…”
Section: Discussionmentioning
confidence: 99%